Bearing Capacity Failure of a Trapezoidal, Geosynthetic-Reinforced Soil Wall. Issue 5 (1st January 1999) - Gopalan, M.; Lo, S.C.R.; Bosler, J.
Abstract : Bearing capacity failure of geosynthetic-reinforced soil walls with a trapezoidal reinforced zone was studied analytically by a series of finite difference stress analyses. Non-associated flow rules and modelling of both construction and the path to collapse were adopted in the analyses. A range of factors, including wall height, soil parameters, and path to failure were studied. For each trapezoidal reinforced soil wall, its equivalent rectangular reinforced wall was also analysed in order to provide a benchmark for evaluation of simplified design models. The results of the analysis were used to calibrate three possible simplified design methods. The performances of these design models were evaluated by the margin of conservatism relative to their equivalent rectangular wall.